OP0272 Identification of New Inhibitors of Angiogenesis in A Novel 3d Model of Rheumatoid Arthritis Synovial Angiogenesis. (15th July 2016) - Maracle, C.X.; Kucharzewska, P.; Helder, B.; Olsson, H.; Tas, S.W.
Abstract : Background: Angiogenesis contributes to rheumatoid arthritis (RA) pathogenesis, however, many models focus solely on endothelial cells (EC). We developed a 3D-spheroid model including both EC and RA fibroblast-like-synoviocytes (FLS) to study angiogenesis associated with RA and to test the efficacy of several inhibitors targeting this process. Previous work demonstrated a role for the non-canonical NF-κB pathway and its main regulator, NF-kB inducing kinase (NIK), in pathological angiogenesis and thus we aim to use the 3D model to further characterize its contribution to neovascularization. Objectives: Generate a representative 3D in vitro model of RA synovial angiogenesis and screen the effects of targeting the non-canonical NF-κB pathway using siRNA or small molecule pharmacological inhibitors. Methods: Human primary EC were co-cultured with RA FLS after pre-incubation with cell tracker dyes and incubated overnight to form spheroids. Subsequently, spheroids were plated in collagen gel and stimulated with 10% RA SF, growth factors (GF) or well-known activators of non-canonical NF-kB signaling (lymphotoxin beta (LT) or LIGHT). To establish NIK dependency, EC were pre-transfected with NIK-targeting siRNA before incorporation into spheroids. Furthermore, several pharmacological inhibitors were screened for their ability to block sprout formation. Spheroids were imaged by confocal microscopy and quantified using Leica QWin Plus software. Results: We established a robust 3D model of angiogenesis containing both EC and RA FLS. LT, LIGHT, RA SF and GF stimulations led to significant increases in sprout formation as compared to basal conditions (p<0.05). The LT and LIGHT induced sprout formation proved to be NIK dependent as spheroids containing EC transfected with NIK targeting siRNA had significant reductions in vessel formation as compared to the non-targeting controls (p<0.05). Sprouting promoted by GF and RA SF was significantly blocked by the angiogenesis inhibitor Anginex (p<0.05). Finally, targeting of the non-canonical pathway using a small molecule pharmacological NIK inhibitor significantly reduced sprout formation caused by LT and LIGHT, and importantly also RA SF-induced sprout formation (p<0.05). Conclusions: We developed a novel 3D model that incorporates essential elements of synovial inflammation, namely EC, RA FLS and RA SF, which proves to be an effective tool for studying synovial angiogenesis. Using this system, we have further demonstrated a role for the non-canonical NF-kB pathway, and its central regulator NIK, in neovascularization associated with RA. Moreover, we have shown that the 3D model is useful for testing small molecule inhibitors of angiogenesis and found that targeting non-canonical NF-kB signaling is an effective method to block pathological angiogenesis. Disclosure of Interest: None declared